1994
DOI: 10.1007/bf02102789
|View full text |Cite
|
Sign up to set email alerts
|

Convergent validity of measures of Post-Traumatic Stress Disorder in a mixed military and civilian population

Abstract: as continuous and dichotomous measures of PTSD in a mired military and civilian group of 70 subjects in the United Kingdom. The MMPI-PTSD and the IES are designed specifically as measures of PTSD and the Global Symptom Index of the SCL-90 i s a general measure of neurosis. All measures produced significant positive correlations with scores from the Clinician Administered Post-Traumatic Stress Disorder Scale (CAPS-1) and with each other. The IES was the most useful dichotomous measure. The optimum cut-off score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 11 publications
3
90
0
1
Order By: Relevance
“…For the entire sample, the IES was 35.0 (±16.1), above the threshold of 19 identified by Horowitz as having severe impact from HIV. In fact, it met the cut off value of 35 reported by Neal et al (1994) for severe PTSD; with about 54.7% above this cut-off.…”
Section: Psychological Functioning At Baselinementioning
confidence: 72%
“…For the entire sample, the IES was 35.0 (±16.1), above the threshold of 19 identified by Horowitz as having severe impact from HIV. In fact, it met the cut off value of 35 reported by Neal et al (1994) for severe PTSD; with about 54.7% above this cut-off.…”
Section: Psychological Functioning At Baselinementioning
confidence: 72%
“…Items are rated on a 5-point scale ranging from 0 (not at all) to 4 (extreme). Cut off scores at or above 35 for a preliminary diagnosis of PTSD have been suggested [54]. The children in this study had mothers with a mean score of 35.1 (SD = 19.1) and about 50% (19 of 37) had mothers with likely PTSD.…”
Section: Methodsmentioning
confidence: 98%
“…The cut-off values for the total scores in the present study are similar to values observed by others. For example, in studies comparing the IES and the Clinician-Administered PTSD Scale (CAPS), Coffey et al (2006) obtained a sensitivity of 0.91 and specificity of 0.72 at a cut-off value of 27, while Neal et al (1994) obtained a sensitivity of 0.89 and a specificity of 0.88 at an optimal cut-off of 35. In the present study, sensitivities of 0.89 and 0.91, respectively, were obtained at an IES cut-off level of 30 (not shown).…”
Section: Scalementioning
confidence: 98%